Innovative Techniques of Digital Crime Investigation - Desai, Shrinivas D.; Narayankar, Prashant (Journal of Engineering Education Transformations, 2016)
Computer forensics is a new and fast growing form of investigative technique in which forensic specialist use modern forensic software tools, to solve digital crime cases. Choosing appropriate forensic tool for solving real-time digital crime cases is most expected graduate attribute, for those who have opted "Computer forensic" as an elective course. In this paper we present pedagogy for developing skill of choosing most appropriate software tool for analyzing and investigating digital crime cases. Assignment activities are designed to develop competencies such as i) Ability to identify, select and apply forensic tool to solve image, audio and video doctored cases. ii) Ability to evaluate the suitability and limitations of the tool used to solve problem. To solve image forensic cases, a tool having feature of error level analysis and meta data analysis is found to be more appropriate, while for solving audio doctored cases, tool having feature of frequency response analysis as well as difference calculator is found to be most appropriate. In case of video doctored crimes, tools having feature of noise analysis, level sweep, clone detection, and magnification is found to be most appropriate. Assessment of outcome is carried out by recording attainment of Graduate Attribute (GA), Competency (CA) and Performance Indicators (PI). Skill of identifying, choosing and applying appropriate forensic tool to solve digital crime cases is observed among student.